2019
DOI: 10.1002/hbm.24525
|View full text |Cite
|
Sign up to set email alerts
|

Maturation changes the excitability and effective connectivity of the frontal lobe: A developmental TMS–EEG study

Abstract: The combination of transcranial magnetic stimulation with simultaneous electroencephalography (TMS–EEG) offers direct neurophysiological insight into excitability and connectivity within neural circuits. However, there have been few developmental TMS–EEG studies to date, and they all have focused on primary motor cortex stimulation. In the present study, we used navigated high‐density TMS–EEG to investigate the maturation of the superior frontal cortex (dorsal premotor cortex [PMd]), which is involved in a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 138 publications
3
8
1
Order By: Relevance
“…Furthermore, trial-by-trial variability for event power was found to significantly decrease across adolescence in both task epochs (Figure 5). These results are in agreement with studies showing decreases in power through adolescence across the cortex 21,[32][33][34][35][36][37] with greater reliability in predicting age than MRI measures 38 . Age-related decreases in power are evident in the beta 21 , theta 39 , and gamma 22 bands with concomitant strengthening of EEG coherence between regions through adolescence 37,40 .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, trial-by-trial variability for event power was found to significantly decrease across adolescence in both task epochs (Figure 5). These results are in agreement with studies showing decreases in power through adolescence across the cortex 21,[32][33][34][35][36][37] with greater reliability in predicting age than MRI measures 38 . Age-related decreases in power are evident in the beta 21 , theta 39 , and gamma 22 bands with concomitant strengthening of EEG coherence between regions through adolescence 37,40 .…”
Section: Discussionsupporting
confidence: 91%
“…The observed lower frontal myelin‐water content might occur in an early stage of the neurodevelopment (ie, related to a genetic component), or might be acquired during or after epilepsy onset (ie, related to epileptiform activity during the vulnerable years of childhood). Although no definite association for the duration of epilepsy was found in this study, the observed abnormality can be interpreted as a neurodevelopmental aspect of the disorder because the maturation of the frontal lobe is still ongoing . Human and animal studies have suggested frontal involvement during the generation or propagation of generalized GSWDs, although the exact brain regions involved are of ongoing debate .…”
Section: Discussioncontrasting
confidence: 66%
“…Although no definite association for the duration of epilepsy was found in this study, the observed abnormality can be interpreted as a neurodevelopmental aspect of the disorder because the maturation of the frontal lobe is still ongoing. 42 Human and animal studies have suggested frontal involvement during the generation or propagation of generalized GSWDs, although the exact brain regions involved are of ongoing debate. 1,2 EEG-functional MRI (fMRI) studies have found different patterns of activation 2 and animal studies point to the somatosensory cortex in the generation of GSWDs.…”
Section: Discussionmentioning
confidence: 99%
“…A number of prior studies have already measured EEG responses to TMS in children (Kallioniemi et al, 2022), but in contexts unconcerned with PCI or consciousness. Although two such studies did report on the complexity of TMS evoked potentials in children (Määttä et al, 2019(Määttä et al, , 2017, the authors appeared to define complexity informally, e.g., based on the number of peaks in the TMS evoked potential, rather than using formal measures such as entropy or LZc. Furthermore, while MRI-guided TMS is safe overall in pediatric populations (Braden et al, 2022), administering TMS to children who do not directly benefit from such stimulation may be ethically ill-advised and, as such, validation efforts in children should only use sPCI without a TMS-based comparison.…”
Section: Ongoing and Future Studiesmentioning
confidence: 99%